The Influence of the Ōjōyōshū in Late Tenth- and Early Eleventh-Century Japan - Horton, Sarah J. (Japanese journal of religious studies, 2004)
Scholars of Heian Buddhism frequently comment that because of the influence of Genshin's Ōjōyōshū, Pure Land thought and practice spread rapidly to all levels of society in the eleventh century. This assertion has become so common that it is rarely questioned. In this article, I investigate eleventh-century sources, such as novels and diaries of aristocrats, and prove that the Ōjōyōshū is mentioned infrequently. The Eiga monogatari, the only text to emphasize the Ōjōyōshū, seems to be the exception to the rule and raises more questions than it answers, since the author is unknown. While agreeing that the Ōjōyōshū was an important work, I conclude that Genshin was a pivotal figure in Heian Pure Land Buddhism less through his authorship of the Ōjōyōshū than through his participation in and leadership of a number of religious fellowships.